CRITICAL REVIEW AND TECHNOLOGY PROPOSAL FOR FUTURE ECONOMIC LASER LATHING - Raja Izamshah, R., Hussein, N. I. S., Zuhair, A., Sivarao, S., Rahim, A.S., Fairuz, D., Hadzley, M.,Amran, M., (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Laser cutting is a thermal process in which a focused laser beam is used to melt material in a localized area. The effectiveness of this process depends on the thermal properties and at certain extent the optical properties rather than mechanical properties of the material. Besides that, laser cutting is one of the advanced manufacturing technology which are capable to machine various materials include metal and non-metal but it has a limitation to cut cylindrical components. Although it has been made possible by the introduction of new laser lathe technology, the cost is exceptionally expensive. The intention of this paper is, therefore, to figure out solutions to the problem of cutting cylindrical components using flat bed laser cutting and to review the laser lathe technology.